1994
DOI: 10.1136/jech.48.4.406
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal caesarean section rate? An outcome based study of existing variation.

Abstract: Study objective -To investigate the consequences of different levels of caesarean section (CS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 19 publications
(13 reference statements)
2
27
0
1
Order By: Relevance
“…It has been suggested that non‐medical factors, such as social, cultural, or unequal accessibility to health services, as well as clinical practice patterns/styles, might have been major contributors to the wide variation in caesarean section rates across different countries 1, 2, 6, 7, 8, 9, 10. On the other hand, we can presume that the rates of medically necessary caesarean section associated with the lowest maternal and neonatal mortality should vary less among countries, if the same indications for caesarean section had been applied across all nations 4, 11. What, then, should be the appropriate caesarean section rate?…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that non‐medical factors, such as social, cultural, or unequal accessibility to health services, as well as clinical practice patterns/styles, might have been major contributors to the wide variation in caesarean section rates across different countries 1, 2, 6, 7, 8, 9, 10. On the other hand, we can presume that the rates of medically necessary caesarean section associated with the lowest maternal and neonatal mortality should vary less among countries, if the same indications for caesarean section had been applied across all nations 4, 11. What, then, should be the appropriate caesarean section rate?…”
Section: Introductionmentioning
confidence: 99%
“…However, there is limited research on the possible relation between hospital obstetric (particularly intrapartum) practice and extended perinatal outcomes. [3][4][5][6][7][8][9] More is known about the links between paediatric neonatal care and mortality. These studies suggest that infants from high risk and low birthweight births are less likely to die if born in more specialised units and that in utero transfers are safer than ex utero.…”
mentioning
confidence: 99%
“…An analysis of pregnancies in one English health region compared groups of obstetric units, categorised according to their caesarean section rates, to see what effect the rate had on a range of outcome variables 5. Care was taken to avoid confounding and selection effects.…”
mentioning
confidence: 99%